Relationship between oral health service quality and patient satisfaction at community health centers in Kupang city during COVID-19 pandemic - Simamora, Friska Deli; Ratu, Jacob Matheos; Roga, Anderias Umbu; Weraman, Pius; Nope, Hotlif Arkilaus (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Oral health service quality has been severely impacted by the COVID-19 pandemic, including in Kupang, one of the cities in the east part of Indonesia. Like in other cities, community health centers (Puskesmas) are the frontline to provide dental healthcare, including avoiding the spread of COVID-19. The objective of this study therefore is to analyze the correlation between oral health service quality  (patient safety, effectiveness, patient centeredness, waiting time, efficiency, and equity) and patients’ satisfaction during COVID-19 pandemic. Methods: Cross sectional design was used to investigate the correlation of oral health services quality and patients’ satisfaction. Structured questionnaire was used to measure patients’ satisfaction. The number of samples involved in this study were fifty people. This study employed a non-probability sampling technique known as incidental sampling. The results of this research were obtained using multivariate multiple logistic regression analysis. Results:  Patients involved in this study consist of women (60%), teenager (50%), adult (40%), educational background is senior high school (56%), junior high school (20%), employment statuses are farmer (30%) and student (28%), monthly average income is < 2 million rupiahs (and government insurance user accounting for 70%). Based on statistical analysis, there is a significant relationship between oral health service quality and patients’ satisfaction (p = 0,002). Conclusion: Patients are satisfied with oral health service quality in Kupang city during COVID-19 pandemic particularly on an equity aspect.Keywords: oral health service quality, patient satisfaction, community health center, COVID-19 pandemic